Pemikiran diskursif amanat agung Injil Matius 28:18-20 - Surya, Agus; Setinawati, Setinawati (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
This paper presents the discursive thinking of the Great Commission of Matthew 28:18-20. A correct understanding of the Great Commission is needed so that the implementation of the preaching of the gospel in society is not arbitrary, let alone cause conflict. This study in exploring the discursiveness of the Great Commission was conducted using a qualitative approach. Retrieval of data in the literature related to the topic in this paper. This research concludes that the discursive Great Commission of the Lord Jesus Christ is one of the culmination of all the biblical foundations for evangelism to develop faith that comes from the four Gospels and the Acts of the Apostles with different emphases. The results of the study conclude that the Gospel of Matthew 28: 18-20 emphasizes that disciples who are weak in faith are empowered to evangelize with the promise of God's participation until the end of time. Abstrak Tulisan ini menyajikan pemikiran diskursif Amanat Agung Matius 28:18-20. Pemahaman yang benar tentang Amanat Agung diperlukan agar implementasi pemberitaan Injil di masyarakat tidak sembarangan, apalagi menyebabkan konflik. Kajian dalam mendalami diskursif Amanat Agung ini dilakukan dengan pendekatan kualitatif. Pengambilan data secara literatur terkait topik dalam tulisan ini. Penelitian ini menyimpulkan, diskursif Amanat Agung Tuhan Yesus Kristus adalah salah satu puncak dari semua dasar Alkitab bagi pekabaran Injil untuk menumbuh kembangkan iman yang bersumber pada ke empat Injil dan Kisah Para Rasul dengan penekanan yang berbeda-beda. Hasil penelitian menyimpulkan bahwa Injil Matius 28: 18-20 menekankan, para murid yang dalam keadaan lemah iman diberi kuasa untuk melakukan penginjilan dengan janji penyertaan Tuhan sampai akhir zaman.